Pemberdayaan Paguyuban Petani Hortikultura melalui Ketahanan Pangan Berbasis Technopreneurship untuk Meningkatkan Perekonomian Desa Karangsari Kabupaten Cilacap - Wulansari, Nuni; Rachmawati, Indra; Yusuf, Dede; Ayun, Ramadhanni Safira Qurrota; Azizah, Nurrahma; Aziz, Khaibar (Lumbung Inovasi: Jurnal Pengabdian kepada Masyarakat, 2025)
Karangsari Village, located in Adipala Subdistrict, Cilacap Regency, is categorized as an area of extreme poverty where the majority of the population works as horticultural farmers. One of the main commodities is pokcoy, a vegetable with a fast harvest cycle. However, overproduction often causes prices to drop drastically, resulting in low farmer income due to dependence on raw product sales. This community empowerment program aims to increase the added value of horticultural products through a technopreneurship approach based on food security. The program was implemented through several stages: socialization, product innovation training, application of appropriate technology, digital marketing training, and business management assistance. The target partner was the Paguyuban Petani Hortikultura Karangsari (Karangsari Horticultural Farmers Association), which previously lacked product diversification, business legality, and effective digital marketing strategies. The program’s results showed a significant improvement in farmers’ knowledge and skills in processing pokcoy into innovative products such as pokcoy powder and pokcoy sticks, applying proper packaging and labeling standards, and utilizing digital media for promotion. The application of technologies such as food dehydrators, grinders, sealers, and the Canva app supported increased productivity and sustainable business development. This program had a positive impact on improving the village’s economy and created opportunities for local-based digital entrepreneurship